The effects of individual innovativeness on users’ adoption of Internet content filtering software and attitudes toward children’s Internet use. - Jin, Chang-Hyun (Computers in Human Behavior, 2013)
Highlights: [•] This paper explores the membership in five adopter categories and users’ adoption of ICFS. [•] Innovators had more favorable perceptions of ICFS than other adopter did. [•] Early adopters had more positive perceptions of ICFS than other adopter did. [•] Innovators and early adopters had greater user satisfaction with ICFS than other adopters did. [•] Innovators and early adopters had greater interest in and control of children’s Internet use.